2020
DOI: 10.1136/annrheumdis-2020-217835
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine shortages during the COVID-19 pandemic

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, conduct, reporting or dissemination plans of this research. Patient consent for publication Not required.Provenance and peer review Not commissioned; internally peer reviewed. This article is made freely available for use in accordance with BMJ's website terms and conditions for the duration of the covid-19 pandemic or until otherwise determined by BMJ. You may use, download and print the article for any lawful, non-comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 3 publications
0
30
0
1
Order By: Relevance
“…241 Similarly, a national survey to Canadian rheumatologists in April, 2020 found that 50-94% of respondents, depending on the region, had been contacted by pharmacies or patients regarding difficulties accessing HCQ. 242 In a patient-centered study in Germany, 70% of 369 respondents expressed concerns about being unable to receive HCQ prescriptions, and 9% had already reduced their HCQ dose in an attempt to overcome potential drug supply issues. 243 One of the main concerns that HCQ shortages prompted was the risk of SLE flares, which are known to occur as soon as D 1 8 7 X X2 weeks after drug discontinuation for most patients with SLE, especially in the younger SLE population.…”
Section: Ancestral Background Socioeconomic Factors and Indirect Conmentioning
confidence: 99%
“…241 Similarly, a national survey to Canadian rheumatologists in April, 2020 found that 50-94% of respondents, depending on the region, had been contacted by pharmacies or patients regarding difficulties accessing HCQ. 242 In a patient-centered study in Germany, 70% of 369 respondents expressed concerns about being unable to receive HCQ prescriptions, and 9% had already reduced their HCQ dose in an attempt to overcome potential drug supply issues. 243 One of the main concerns that HCQ shortages prompted was the risk of SLE flares, which are known to occur as soon as D 1 8 7 X X2 weeks after drug discontinuation for most patients with SLE, especially in the younger SLE population.…”
Section: Ancestral Background Socioeconomic Factors and Indirect Conmentioning
confidence: 99%
“…2 We previously reported that rheumatologists in most Canadian provinces observed HCQ shortages early in the COVID-19 pandemic. 3 However, data are lacking on the global experience with HCQ access during the pandemic, specifically in SLE.…”
mentioning
confidence: 99%
“…More than half of respondents taking HCQ reported difficulties accessing their prescription between March and May 2020 (27). Reports of HCQ shortages and concerns about rheumatology patients' access have also been reported in Canada (28) and countries across Europe (2) and the Middle East (29). Although we do not yet know the full extent of the impact that barriers to HCQ access and shortages have had on patients, serious adverse effects can result from withdrawal in patients with SLE, for which HCQ is a cornerstone of treatment (30).…”
Section: 00mentioning
confidence: 99%